Beyond the Zagreb indices. Issue 1 (2nd January 2020) - Gutman, Ivan; Milovanović, Emina; Milovanović, Igor
Abstract: The two Zagreb indices M 1 = ∑ v d ( v ) 2 and M 2 = ∑ u v d ( u ) d ( v ) are vertex-degree-based graph invariants that have been introduced in the 1970s and extensively studied ever since. In the last few years, a variety of modifications of M 1 and M 2 were put forward. The present survey of these modified Zagreb indices outlines their main mathematical properties, and provides an exhaustive bibliography.